Lithium in Drinking Water as a Public Policy for Suicide Prevention: Relevance and Considerations - Araya, Pablo; Martínez, Camila; Barros, Jorge (Frontiers in Public Health, 2022)
Although suicide is considered a major preventable cause of mortality worldwide, we do not have effective strategies to prevent it. Lithium has been consistently associated with lowering risk of suicide. This effect could occur at very low concentrations, such as trace doses of lithium in tap water. Several ecological studies and recent meta-analysis have suggested an inverse association between lithium in water and suicide in the general population, with a lack of knowledge of clinically significant side effects. This paper is aimed as a proposal to discuss the addition of lithium to drinking water to decrease the suicide rate. For this, we review the evidence available, use previous experiences, such as water fluoridation to prevent dental caries, and discuss the complexity involved in such a public policy. Considering the limited data available and the controversies contained in this proposal, we suggest that a consensus on lithium concentration in water is needed, where the suicide rates start to reduce, as happened with water fluoridation. This measure will require to develop community-controlled trials with strict monitoring of any side effects, where democratic procedures would constitute one of the most appropriate ways to validate its implementation according to the reality of each community.